Live Cell Membranome cDNA Screen: A Novel Homogenous Live Cell Binding Assay to Study Membrane Protein-Ligand Interaction. (December 2019) - Shen, Xun; Smith, Elizabeth; Ai, Xi; McElroy, William T.; Liaw, Andy; Kreamer, Tony; Chang, Meiping; Devito, Kristine; Hudak, Edward; Xu, Serena; Pei, Yi; Sur, Sylvie; et al.
Interactions between transmembrane receptors and their ligands play important roles in normal biological processes and pathological conditions. However, the binding partners for many transmembrane-like proteins remain elusive. To identify potential ligands of these orphan receptors, we developed a screening platform using a homogenous nonwash binding assay in live cells. A collection of 1900 cDNA clones, encoding full-length membrane proteins, was assembled. As a proof of concept, cDNA clones were individually transfected into CHO-K1 cells in a high-throughput format, and soluble PD-L1-Fc fusion protein was used as bait. The interaction between the putative receptor and PD-L1-Fc was then detected by Alexa Fluor 647 conjugated anti-human immunoglobulin G Fc antibody and visualized using the Mirrorball fluorescence plate cytometer. As expected, PDCD1, the gene encoding programmed cell death protein 1 (PD-1), was revealed as the predominant hit. In addition, three genes that encode Fc receptors (FCGR1A, FCGR1B, and FCGR2A) were also identified as screen hits as the result of the Fc-tag fused to PD-L1, which has provided a reliable internal control for the screen. Furthermore, the potential of using a biotinylated ligand was explored and established to expand the versatility of the cDNA platform. This novel screening platform not only provides a powerful tool for the identification of ligands for orphan receptors but also has the potential for small-molecule target deconvolution.